Implementasi Sistem Administrasi dan Inventory Control pada Warehouse UD. X - Michael Pang; Lily Puspa Dewi; Yulia Yulia (Jurnal Infra, 2021)
Inventory control is a process to ensure the amount of supply available in a business process. Inventory control can help prevent losses and turnover and maximize customer satisfaction. The problems experienced by UD Warehouse. X is prone to stockout and inaccurate transaction recording. Inventory control and administration systems will be used to help avoid stockouts and record transactions accurately. Based on the transactions that have been recorded in the system, it can produce the ideal number of goods procured along with when the goods are procured. Reports for each period can be seen on the system in accordance with the recording of transaction data. The data used in calculating Economic Order Quantity and Reorder Point are transactions from 2018 at the UD warehouse. X.